PENINGKATAN PEMAHAMAN KONSEP PKN MATERI LEMBAGA NEGARA DENGAN MEDIA CHART PADA SISWA KELAS VI SD N 1 TAWANGHARJO - Supriyanto.Th . (Universitas PGRI Yogyakarta, 2020)
AbstractThe purpose of this study is to improve the quality of the learning process and improve students' understanding of concepts so that learning outcomes can improve. This research was conducted through a Classroom Action Research procedure with four stages of activities ranging from planning, implementing, observing, and reflecting. The data analysis is done by comparing the initial conditions with the first cycle where there is an increase from an average value of 60 to 69.09 and comparing between the first cycle with the second cycle an increase from an average value of 69.09 to 82.73 and compare from initial conditions until the second cycle an increase of an average of 82%. Thus the results of the study showed that by applying the contextual approach students more quickly understood the concepts conveyed in learning, so that learning outcomes improved.Keywords: PKN, RI State Institution, Media Chart